Cutaneous anthrax rapidly progressed into septic anthrax resulting in death – A case report - Yufei Lyu; Shiyuan Li; Dongshu Wang; Meijie Feng; Wenjun Li; Xiankai Liu; Jia Zhou; Li Nie; Chao Pan; Shujuan Yu; Yan Guo; Hua Shao (IDCases)
Anthrax is a fatal zoonotic disease and the acute risk associated with it cannot be underestimated. Cutaneous anthrax accounts for more than 95 % of anthrax and usually does not lead to death. We present a case of severe cutaneous anthrax treated with a three-day course of combination antibiotics therapy, which culminated into death due to multiple organ failure. The patient did not exhibit symptoms suspected of meningitis anthrax and pulmonary anthrax. Computed Tomography revealed subcutaneous exudates in the chest, back, left supraclavicular fossa, and bilateral axillary regions. Some newly factors, like hypotension, elevated creatinine, acidosis, and a urinary tract infection, provide valuable insights into the clinical intervention in early. In rural areas, educating residents about anthrax symptoms and risks is crucial.